Recognition‐Induced Enhanced Emission of Core‐Fluorescent ESIPT‐type Macrocycles. Issue 2 (14th November 2022) - Jurek, Paulina; Jędrzejewska, Hanna; Rode, Michał F.; Szumna, Agnieszka
Abstract: Core‐fluorescent cavitands based on 2‐(2′‐resorcinol)benzimidazole fluorophores (RBI s) merged with the resorcin[4]arene skeleton were designed and synthesized. The cavitands, due to the presence of intramolecular hydrogen bonds and increased acidity, show excited state intramolecular proton transfer (ESIPT) and readily undergo deprotonation to form dianionic cavitands, capable of strong binding to organic cations. The changes in fluorescence are induced by deprotonation and binding events and involve huge Stokes shifts (due to emission from anionic double keto tautomers) and cation‐selective enhancement of emission originating from the restriction of intramolecular motion (RIR) upon recognition in the cavity. Ab initio calculations indicate that the macrocyclic scaffold stabilizes the ground state tautomeric forms of the fluorophores that are not observed for non‐macrocyclic analogs. In the excited state, the emitting forms for both macrocyclic scaffolds and non‐macrocyclic analogs are anionic double keto tautomers, which are the result of excited state intramolecular proton transfer (ESIPT) or excited state double proton transfer (ESDPT). Abstract : ESIPT‐type resorcin[4]arenes are capable of guest‐binding in the cavity and generate FL response with large Stokes shift and size‐selective enhancement of emission via the mechanism that involves (a) selective di‐deprotonation, (b) generation of emissive double keto tautomeric forms, and (c) recognition‐induced restriction of intramolecular motion.